Assessing The Impact Of Pharmacist Assistant - Led Medication Counseling On Adherence In Patients With Hypertension - Naif Mesfer Alzahrani , Saleh Hadi Alhasani , Mohammed Abdullah Alghamdi , Mohammed Ahmed Almirabi , Ahmed Oudah Alghamdi, Mohammed Abdulmohsen Alhazmi, (Migration Letters, 2022)
Hypertension is a chronic medical condition that increases the risks of heart disease and stroke. It is estimated that over 1.13 billion people suffer from hypertension worldwide, with the prevalence continuing to rise. The objective of this review was to evaluate medication adherence rates among hypertensive outpatients at a large tertiary hospital and identify patient characteristics associated with non-adherence. Pharmacist interventions incorporating patient education, medication reconciliation, lifestyle modifications and regular monitoring were found to reduce systolic blood pressure by 8.1 mmHg. Existing evidence indicates pharmacist-led counseling programs incorporating patient education, medication reviews and motivational interviewing techniques are effective in improving medication adherence and clinical[1] outcomes in patients with hypertension. This study utilized a single-center, randomized controlled trial design. Hypertensive out patients aged 30-75 years who had been prescribed at least one antihypertensive medication for ≥3 months were recruited from a large tertiary hospital clinic from January 2020 to December 2020. A total of 200 patients were included in the analysis (100 in the intervention group, 100 in the control group). Baseline characteristics were similar between the two groups. Our results demonstrate pharmacist assistant-led counseling significantly improved medication adherence and clinical outcomes in hypertensive patients compared to usual care. The intervention had additive benefits on blood pressure control, quality of life, and healthcare costs. Our findings suggest pharmacist assistant-led counseling is an effective strategy for enhancing medication adherence and hypertension management. With additional benefits observed in clinical, quality of life and economic outcomes, the intervention shows promise as a valuable addition to usual care. However, several limitations must be noted. The single-center setting and inclusion of a predominantly urban population may limit generalizability. Despite limitations, the multicomponent intervention could be adapted for broader implementation. Community pharmacists are well-positioned to deliver counseling and address barriers like access faced by disadvantaged groups. Further research should evaluate scalability, optimal frequency/duration of counseling, and cost-effectiveness. Longer follow-up would also assess if benefits are sustained over time. In conclusion, pharmacist assistant-led counseling shows promise as a strategy to improve hypertension outcomes. With refinement and broader testing, it warrants consideration for inclusion in clinical guidelines and reimbursement models. Future research in this area could involve longer term follow-up to establish durability of effects over time. Cost-effectiveness analyses incorporating societal and healthcare sector perspectives would aid decision making regarding reimbursement and resource allocation. Studies evaluating scalability and optimal implementation in community pharmacy settings are also warranted. Overall, pharmacist assistant-led counseling demonstrates potential as an effective quality improvement intervention deserving consideration for inclusion in clinical guidelines and practice.